Influence of Organisational Behaviour, Organisational Development, Organisational Culture and Leadership Style and Its Impact on Motivation in Public Organisation - Muthuswamy, Vimala Venugopal (Journal of Ecohumanism, 2024)
One of the objectives of this research is to examine the relationship between organizational behavior and employee motivation, to highlight the relationship between organizational culture and employee motivation, to elaborate on the relationship between leadership style and employee’s motivation, and to investigate the relationship between organizational development and employee motivation. This research also works to investigate the role of leader in the organization. As we know, leaders are the people who are responsible for selecting a path for the whole organization. The researcher collect 113 samples from leaders in Public organization in India. The questionnaire was prepared by using Google Docs application. The survey questionnaires were distributed to more than 200 participants; 113 responses were received from participants. The researcher use descriptive statistics and Multiple regression analysis to test the hypothesis. This study is an attempt to explore the factors that affect and help motivate employees working in any organization, as it is necessary to strengthen these institutions by establishing the principles of Leadership Style, Organizational Culture and Work Environment, Organizational Behavior and Organizational Development.Leadership style